Primary Care as Primary Target: A Review of Terrorist Attacks Against Primary Care Providers and Their Offices. Issue 4 (1st August 2022) - Wirken, Bart; Barten, Dennis G.; De Cauwer, Harald; Mortelmans, Luc J.M.; Tin, Derrick; Cals, Jochen
Abstract: Background: Violence against primary care providers (PCPs) has increased during the current pandemic. While some of these violent acts are not defined as terrorist events, they are intentional events with an aim to disrupt, kill, or injure. Despite their pivotal role in health care, little is known about the risk for PCPs as targets of terrorism. Methods: Data collection was performed using a retrospective database search through the Global Terrorism Database (GTD). The GTD was searched using the internal database search functions for all terrorist attacks against PCPs and their offices from January 1, 1970 - December 31, 2019. Years 2020 and 2021 were not yet available at the time of the study. Primary attack and weapon type, location (country, world region), and number of deaths and injuries were collated. Results were exported into an Excel spreadsheet (Microsoft Corp.; Redmond, Washington USA) for analysis. Results: There were 29 terrorist attacks against PCPs and their offices from 1970-2019. The majority of attacks occurred during or after 2010. There were 58 fatalities, 52 injured, and 13 hostages. Most documented attacks took place in Pakistan, the United States, and Sri Lanka. Bombings concerned 55% of cases and 21% were hostage-takings. Conclusion: Although less common than attacks on other health care related targets, terrorist attacks against PCPs have occurred. The majority of attacks occurred during the last decade. Future studies are warranted to further assess the risk of terrorist attacks against PCPs: before, during, and beyond the current pandemic.